Gathering data for decisions: best practice use of primary care electronic records for research. (30th March 2019) - Canaway, Rachel; Boyle, Douglas IR; Manski‐Nankervis, Jo‐Anne E; Bell, Jessica; Hocking, Jane S; Clarke, Ken; Clark, Malcolm; Gunn, Jane M; Emery, Jon D
Summary: In Australia, there is limited use of primary health care data for research and for data linkage between health care settings. This puts Australia behind many developed countries. In addition, without use of primary health care data for research, knowledge about patients' journeys through the health care system is limited. There is growing momentum to establish "big data" repositories of primary care clinical data to enable data linkage, primary care and population health research, and quality assurance activities. However, little research has been conducted on the general public's and practitioners' concerns about secondary use of electronic health records in Australia. International studies have identified barriers to use of general practice patient records for research. These include legal, technical, ethical, social and resource‐related issues. Examples include concerns about privacy protection, data security, data custodians and the motives for collecting data, as well as a lack of incentives for general practitioners to share data. Addressing barriers may help define good practices for appropriate use of health data for research. Any model for general practice data sharing for research should be underpinned by transparency and a strong legal, ethical, governance and data security framework. Mechanisms to collect electronic medical records in ethical, secure and privacy‐controlled ways are available. Before the potential benefits of health‐related data research can be realised, Australians should be well informed of the risks and benefits so that the necessary social licence can be generated to support such endeavours.